Deployment of treated and compressed biogas as a sustainable fuel for ceramic kiln firing - Ezra Abubakar; Rahmatu Yunusa Shariff; Yusuf Otaru Sadiq (Center for Science and Technology, IAIN Surakarta, 2022)
Inefficiency, emission of greenhouses gases and the deleterious effects of carbonaceous fuels on both human health and the environment are responsible for the increased in exploration and adoption of eco-friendly and sustainable fuels to various aspects of human development and production processes. This study was aimed at the generation, treatment and compressing of biogas into Liquefied Petroleum Gas Cylinder (LPGC) for deployment to firing ceramic kiln. The methodology involved the anaerobic digestion of cow dung and the treatment of the generated gas using water scrubbing technology. The results of the study showed an increased in methane content from an untreated value of 43.5% to 93.98%, the elimination of CO2, and H2S; reduction in volume of gas used in firing a ceramic kiln to 1030 Â°C from 22,300 L of untreated biogas to 492 L of treated biogas, as well as the prevention of 108,000 g of methane, 124,00 g of CO2, 74,400 g of CO and 173.6 g of NO2 from venting into the climate system.